(untitled) (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2025)
This article provides a comparative of Sadriddin Ayni’s “Doxunda” and Ernest Hemingway’s “The Old Man and the Sea”, focusing on universal human struggles and the search for meaning across two contrasting literary traditions. Through the lens of comparative literature, the article analyzes thematic structures, character development, narrative technique, and socio-cultural contexts to understand how each text represents hardship and resilience. Despite their different environments and literary movements, both texts emphasize the human capacity to endure loss, confront adversity, and construct meaning in suffering. The study demonstrates that comparative reading highlights cross-cultural patterns of resilience and expands the interpretive possibilities of each text. This article argues that the juxtaposition of these works reveals how literature universally reflects the human experience while remaining deeply connected to specific cultural histories.